Lateral Meniscus Allograft Transplantation in a Skeletally Immature Patient - Curtis VandenBerg MD; Bert Mandelbaum MD, DHL; Sarah Stelma MD; Stockton Troyer BS; Kevin Collon MD; Kevin Shea MD (SAGE Publishing, 2022)
Background: Lateral meniscus deficiency in young patients typically results from irreparable lateral meniscus tears, often associated with discoid meniscus. Such cases present a challenging clinical scenario given the known natural history of meniscus deficiency leading to degenerative lateral knee compartment changes. Managing this problem in a skeletally immature patient presents additional clinical and surgical considerations. Indications: Lateral meniscus allograft transplantation (LMAT) is indicated in patients with prior total or subtotal lateral meniscectomy resulting from irreparable lateral meniscus tears, with the goal of providing chondroprotection to the lateral compartment of the knee. Patients are assessed preoperatively for ligamentous stability of the knee, mechanical alignment, and associated chondral injuries to determine whether secondary procedures may be indicated. Technique Description: We present an all-arthroscopic technique for LMAT using small bone plugs in the anterior and posterior meniscus roots secured through 2 separate anatomic root drill tunnels tied over a bone bridge. The meniscus allograft is further secured using an outside-in suture repair technique. Special attention is given to meniscus allograft preparation, anatomic meniscus root identification, and drilling using a minimally disruptive transphyseal technique. Graft passage, suture management, and meniscus fixation and repair are also highlighted. Results: Anticipated outcomes from LMAT in skeletally mature patients are excellent, particularly if preexisting chondral degenerative changes are not present. Prior studies with greater than 7-year follow-up in adolescent patients undergoing meniscus allograft transplantation have shown reoperation rates of less than 6% with no growth disturbances noted, with most patients able to return to their prior level of sport. Computed tomography modeling data using this technique shows a proximal tibial physeal surface area disruption of less than 2.5%; therefore, the risk of growth disturbance is very low. Discussion/Conclusion: The surgical technique demonstrated here offers a safe and effective approach for the management of lateral meniscus deficiency after subtotal lateral meniscectomy for irreparable meniscus tears in skeletally immature patients. The chondroprotective effect of the lateral meniscus can be restored with an anatomically placed lateral meniscus allograft with minimal disruption to the proximal tibial physis.